OPTIMIZING THE ROLE OF FINDING AIDS IN ENHANCING THE EFFECTIVENESS OF ELECTRONIC RECORDS MANAGEMENT AT MUHAMMADIYAH UNIVERSITY OF JAKARTA - Nidaul Haq; Tamara Adriani Salim (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
The transformation of archive management to an electronic system requires the existence of effective digital finding aids to support access and retrieval of archives (archival retrieval systems). This study aims to analyze the role of digital finding aids in the E-Archives system of Muhammadiyah University of Jakarta (UMJ). The study used a descriptive qualitative approach with application developers, archive managers, and system users as subjects. Data were collected through observation, interviews, and documentation. Data analysis refers to the interactive model of Matthew B. Miles et al. which includes data reduction, presentation, and iterative drawing and verification of conclusions. Data validity was maintained through triangulation of sources and techniques. The results show that the UMJ E-Archives has implemented basic elements of digital finding aids such as metadata, classification, and search features. However, its effectiveness still needs to be improved through metadata standardization, enrichment of archive descriptions, and adjustments to user needs. The novelty of this study lies in the integration of system analysis and user experience, with practical contributions in the form of recommendations for developing a more structured and user-oriented archive system.